Preliminary findings aiming at investigating ex-ante the impact of policy measures on CGIAR accessions - Gotor, Elisabetta (2021)
Purpose of the Study: 1. Investigate the ex-ante impact of the revision of the Multilateral System of Access and Benefit Sharing of plant genetic resources for food and agriculture on CGIAR Centers 2. Identify measures to respond to possible negative impacts on CGIAR Centers as recipients and providers of germplasm and associated information under the multilateral system.